Passive and active ventricular elastances of the left ventricle - Zhong, Liang (2016)
Background: Description of the heart as a pump has been dominated by models based on elastance and compliance. Here, we are presenting a somewhat new concept of time-varying passive and active elastance. The mathematical basis of time-varying elastance of the ventricle is presented. We have defined elastance in terms of the relationship between ventricular pressure and volume, as: dP = EdV + VdE, where E includes passive (Ep) and active (Ea) elastance. By incorporating this concept in left ventricular (LV) models to simulate filling and systolic phases, we have obtained the time-varying expression for Ea and the LV-volume dependent expression for Ep.Methods and Results: Using the patient's catheterization-ventriculogram data, the values of passive and active elastance are computed. Ea is expressed as: https://static-content.springer.com/image/art%3A10.1186%2F1475-925X-4-10/MediaObjects/12938_2004_Article_82_IEq1_HTML.gif ; Epis represented as: https://static-content.springer.com/image/art%3A10.1186%2F1475-925X-4-10/MediaObjects/12938_2004_Article_82_IEq2_HTML.gif . Ea is deemed to represent a measure of LV contractility. Hence, Peak dP/dt and ejection fraction (EF) are computed from the monitored data and used as the traditional measures of LV contractility. When our computed peak active elastance (Ea,max) is compared against these traditional indices by linear regression, a high degree of correlation is obtained. As regards Ep, it constitutes a volume-dependent stiffness property of the LV, and is deemed to represent resistance-to-filling. Conclusions: Passive and active ventricular elastance formulae can be evaluated from a single-beat P-V data by means of a simple-to-apply LV model. The active elastance (Ea) can be used to characterize the ventricle's contractile state, while passive elastance (Ep) can represent a measure of resistance-to-filling.